ANALISIS STRATEGI COST LEADERSHIP PADA PT. AJE INDONESIA - KHUSNA, (Jurnal Akuntansi AKUNESA, 2015)
Company can do a generic strategies to achieve competitive advantage. Michael R. Porter divided the strategy into three, there are differentiation, Cost Leadership and Focus. Cost Leadership is a company's strategy to minimize cost so that the cost incurred lower than the company which use Differentation strategy or Focus. Application of Cost Leadership strategy can improve the performance of the company. This research was conducted at PT. AJE INDONESIA which produces beverage Big Cola and analyze how the company can manage the cost like production cost and non-production cost. Production cost such as raw material costs, labor costs and overhead costs and non-production cost like marketing expenses and general administration. The results showed that the strategy of Cost Leadership is achieved by strict cost control and thorough.Keyword: Cost Leadership